2014
DOI: 10.1016/j.nrl.2012.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Marcaje colinérgico en la corteza cerebral y el hipocampo en algunas especies animales y su relación con la enfermedad de Alzheimer

Abstract: This paper reviews the main immunomorphological studies of the cerebral cortex and hippocampus in some animal species with particular emphasis on the cholinergic system and its relationship with the AD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(4 citation statements)
references
References 36 publications
0
3
0
1
Order By: Relevance
“…Cumulative evidence has suggested that cognitive dysfunction in AD is the result of impaired neurogenesis in the hippocampus of the adult brain, and it is crucial to identify novel drugs that can be used for the treatment of AD [27,28]. The cholinergic function is reduced in the forebrain, especially in the hippocampus, and a change in AChE activity in the hippocampus is usually a biomarker for diagnosing AD [29]. SCO impairs memory in rodents and humans, which interferes with the cholinergic system, including ACh, and causes oxidative stress, leading to cognitive dysfunction [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cumulative evidence has suggested that cognitive dysfunction in AD is the result of impaired neurogenesis in the hippocampus of the adult brain, and it is crucial to identify novel drugs that can be used for the treatment of AD [27,28]. The cholinergic function is reduced in the forebrain, especially in the hippocampus, and a change in AChE activity in the hippocampus is usually a biomarker for diagnosing AD [29]. SCO impairs memory in rodents and humans, which interferes with the cholinergic system, including ACh, and causes oxidative stress, leading to cognitive dysfunction [30,31,32].…”
Section: Discussionmentioning
confidence: 99%
“…AD is highly related to cholinergic system impairment and intracellular oxidative stress [7,29]. Hippocampal cholinergic dysfunction has been identified in neurodegenerative diseases that are characterized by memory impairment, including AD, and in animal experiments [33,34].…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, ChAT can help to catalyze the biosynthesis of acetylcholine [29]. Thus changes in AChE and ChAT activities are often used as cholinergic biomarkers for diagnose AD [30]. In this study, walnut oil treatment significantly inhibited AChE activity and promoted ChAT activity in the brain of cognitive deficient mice.…”
Section: Discussionmentioning
confidence: 71%
“…Una de las funciones elementales de la vía colinérgica se basa en la regulación del ciclo de vigilia y sueño, así como en la modulación de los procesos de aprendizaje y memoria, de forma que la disfunción de la neurotransmisión colinérgica supone una hipótesis explicativa sobre la aparición de los déficits cognitivos y de la gravedad de la EA (Orta-Salazar, Cuellar-Lemus, Díaz-Cintra & Feria-Velasco, 2014). Datos recientes apuntan a una redefinición de la hipótesis colinérgica en la que el déficit colinérgico impide al cerebro la capacidad de compensación frente a otros factores de riesgo neuropatológicos concomitantes (Craig, Hong & McDonald, 2011) y es susceptible de ser investigada mediante la pupilometría (Fotiou, Kaltsatou, Tsiptsios, Nakou, 2015).…”
Section: Hipótesis Colinérgicaunclassified